(untitled) (Jurnal Sosial Ekonomi Pertanian, 2022)
The horticulture sub-sector as one of the leading sub-sectors in agricultural development has grown and developed into a commodity that is quite attractive to the market. One of the supporting factors for the development of horticultural agribusiness is the empowerment of farmers through institutional development. To be able to formulate appropriate institutional forms, understanding community institutions is an important first step. Understanding of institutions is done by identifying local institutions, their potentials and roles. This understanding will make it easier to formulate strategies for strengthening local institutions. Good institutional quality will have an effect on managing the horticultural agribusiness that is involved. Recently, institutions have become very valuable because the implementation of development in the modern era is always correlated with institutions or organizations that are formed as a vehicle for transferring capital and technology. The objectives of this research are: 1). The identification of local institutions in the development of horticultural agribusiness in Bantaeng Regency, 2). Knowing the strategy of institutional strengthening in the development of horticultural agribusiness in Bantaeng Regency. The data analysis used in this research is descriptive qualitative analysis with SWOT data analysis technique. Local institutions that exist to support the development of horticultural agribusiness include Public Sector institutions (BP3K, Food Security Agency and Extension Officer and Agriculture Service). Voluntary Sector Institutions (Farmers’ Group, Women’s Farmer’s Group, Association of Farmers’ Groups, Village Unit Cooperatives and Farmers’ Cooperatives). Private Sector Institutions (Retailer and Joint Business Groups). Strategies that need to be implemented in strengthening local agribusiness institutions are continuous improvement of institutional human resources and involvement of young farmers in the management structure of agribusiness institutions, training in digital-based institutional management management training, increasing collaboration with financial institutions and utilizing government support to the fullest, maximizing institutional roles and functions as well as institutional administrators and increase institutional awareness for all members and improve services to all group members and consumers. Keywords: Strengthening, Local Institutions, Horticultural Agribusiness